Distortions to Agricultural Incentives in Bangladesh - Ahmed, Nazneen (Washington, DC : World Bank, 2022)
Bangladesh has substantially liberalized its trade and agricultural pricing policies since independence in 1971, removing most distortions to agricultural incentives by the mid-1990s. Although trade protection for some agricultural and industrial products has increased sharply since 1998, total distortions in agriculture remain small. In particular, domestic and international trade policies for the major staples, rice and wheat, are substantially more liberal than in Pakistan or India. In the early 1970s, Bangladesh pursued a highly restrictive trade and exchange rate policy characterized by import regulations, high import tariffs, export taxes, pervasive quantitative restrictions, and an overvalued exchange rate, similar to policies of the 1960s when it was part of united Pakistan. The policy regime in the 1970s was especially restrictive for the agricultural sector. The government had a monopoly on import of most agricultural commodities and placed major restrictions on exports of raw jute, the major agricultural export. As a result of these distortions, agricultural price incentives were substantially reduced throughout the period (Rahman 1994). This chapter describes the changing structure of distortions to agricultural incentives in Bangladesh, and the forces that have driven it. The next section describes the growth and structural changes of the Bangladesh economy with particular emphasis on the agricultural sector. An overview of the evolution of agricultural policies in Bangladesh since independence is then provided, before reporting time series of estimates of nominal rates of assistance (NRAs) for selected agricultural products. The changing political economy of agricultural price and trade policies is then discussed, followed by some concluding observations.